STRATEGY TO IMPROVE THE WASTE MANAGEMENT COMPANY CASE STUDY: CV BINA USAHA MANDIRI - Fatma Nur Rosana; Harimukti Wandebori (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
Solid waste management (SWM) poses a significant environmental issue in Indonesia, with increasing waste generation and limited infrastructure leading to environmental contamination. The government's initiatives and waste management companies aim to address this issue by encouraging public participation. However, many community-based initiatives face challenges in sustainability and development. This study focuses on analyzing the business model of CV Bina Usaha Mandiri (BUM), a waste management company in Central Java, to provide a development plan for effective waste management services. This study was conducted using a qualitative approach to understand the challenges faced by the business owner, then explore how to improve their performance and provide ideas. The data was analyzed qualitatively by adopting an inductive approach with the purpose of developing conclusions from the collected data. External and internal environments were analyzed, then SWOT analysis was used to assess BUM's competitiveness in order to develop a business strategy. Based on the SWOT matrix, some strategies are selected to be proposed for BUM performance improvement concerning the collection volume and their business management. The study recommends the adoption of a focus differentiation strategy for BUM. Leveraging its solid presence in Central Java and Yogyakarta, BUM's strength in providing unique services for handling low-value materials positions it to gain a competitive advantage.